Factors associated with the critical thinking ability of professional nurses: A cross‐sectional study - Tuan Van Nguyen; Hsueh‐Erh Liu (Wiley, 2021)
Abstract Aim To measure the level of critical thinking among Vietnamese professional nurses and to identify the related factors. Design A cross‐sectional design was used. Methods The total sample included 420 professional nurses. Data were collected from July to September 2019 in three public hospitals located in Southwestern Vietnam. The level of critical thinking was measured using the Vietnamese version of the Nursing Critical Thinking in Clinical Practice Questionnaire. The data were analysed using the independent Student's t tests, ANOVA, Pearson's correlation and regression analysis. Results Most of the participants had a low (48.3%) or moderate (45.5%) level of critical thinking. Age, gender, ethnicity, education level, health condition, duration of working as a nurse, duration of working in the current hospital, having heard the term "critical thinking" and work position had an impact on the critical thinking ability. Work position and gender explained 11% of the total variance in critical thinking ability.